The Adequacy of Legal Regulation of Acquisition and Consortium as a Mean of Economic Focus in Jordanian Legislation: A Comparative Study - Noor Mohammed Al-Daraweesh (Britain International for Academic Research (BIAR-Publisher), 2023)
The economic focus of commercial companies is one of the mechanisms and means that resulted in modern legal thought, relative to the inclusion of innovative economic methods represented by the conglomeration of companies and small and large commercial establishments under the umbrella of a giant company with a tight legal framework that defines the provisions related to the procedures and the effects of such gatherings and economic blocs that rule over Huge capitals have a profound impact on economic growth at the national and global levels, and the need has emerged to surround the economic concentration operations of companies with this tight legislative framework in light of the radical changes that the global economic system has witnessed as a result of the globalization of competition. Community Verified icon, And the special principles it stipulated in the field of trade liberalization, which prompted companies to unite in the form of large conglomerates in order to preserve their presence in the market and face the economic crises that they may be exposed to, since their survival on their own has become a useless choice and rather a danger to them, given the simple capabilities and Ltd. that it owns and which will not help it pay the risk on its behalf.